Psoas density - an optimal sarcopaenic indicator associated with postoperative complications after colorectal resection for cancer? - Pekařová, Anna; Pekař, Matej; Soltes, Marek; Havrlentová, Lucia; Chovancová, Tereza (Wideochirurgia i inne techniki maloinwazyjne, 2021)
INTRODUCTION: Sarcopaenia seems to be predictive factor for postoperative morbidity and mortality after colorectal resection for cancer. Nevertheless, an ideal sarcopaenic indicator is still to be identified. AIM: To evaluate computed tomography (CT) measured total abdominal muscle area (TAMA), total psoas muscle area (TPA), and psoas density (PD) - previously described sarcopaenia indicators - as possible risk factors for postoperative complications in patients after curative colon and rectal resections for colorectal cancer. MATERIAL AND METHODS: Consecutive patients after elective curative colon or rectal resection for cancer at a single institution were divided into cohorts with uncomplicated postoperative course or complications Clavien-Dindo grade I-II (Cl-Di 0-II) and complications Clavien-Dindo grade III-V (Cl-Di III-V). Cohorts were statistically tested for significant differences in TAMA, TPA, and PD calculated from preoperative staging CT scans at the level of the third lumbar vertebra. RESULTS: Data of 112 patients were analysed from a prospectively run database; 65 underwent colon and 47 rectal resections. PD was significantly higher in the Cl-Di 0-II cohort compared to the Cl-Di III-V for both colon (42.67 ±6.52 vs. 40.11 ±7.57 HU, p = 0.002) and rectal resections (44.08 ±5.86 vs. 43.03 ±5.70HU, p = 0.016). TAMA and TPA failed to show significant differences. CONCLUSIONS: Psoas density is significantly decreased in patients with Clavien-Dindo grade III-V complications after curative resection for colon and rectal cancer. Due to the simplicity and affordability of its assessment from preoperative staging CT scan, it might be considered an optimal sarcopaenic indicator to be utilised in everyday practice.
Keywords: psoas density; computed tomography; complications; sarcopaenia; colorectal cancer